Recombinant Analogue of Envelope Glycoprotein Domain III of the Tick-Borne Encephalitis Virus and its Application for the Differential Diagnosis of Flavivirus Infections - A. G. Poltavchenko; A. V. Ersh; P. V. Filatov; N. D. Ushkalenko; D. V. Shan’shin; D. N. Shcherbakov (Проблемы особо опасных инфекций)
Tick-borne encephalitis is a flavivirus disease, endemic to vast areas of Europe and Asia, caused by the tick-borne encephalitis virus from the genus Orthoflavivirus, transmitted through the bite of a tick. The course of infection is characterized by fever followed by the development of potentially fatal encephalitis. Serological diagnosis of tick-borne encephalitis is complicated by severe cross-reactivity with antibodies to other endemic and imported flavivirus infections. The aim of the study was to obtain a recombinant analogue of domain III of the surface protein E of the tick-borne encephalitis virus (EDIII-TBEV) and assess its ability to detect antibodies to the tick-borne encephalitis virus and differentiate them from antibodies to other flavivirus infections. Materials and methods. A comparative study was performed using panels of sera containing and not containing antibodies to the tick-borne encephalitis virus, and panels of samples with antibodies to yellow fever, dengue, and Zika viruses. The study was conducted using commercial tests and experimental kits based on EDIII-TBEV in the ELISA format and in the dot analysis format. Results and discussion. It has been shown that the use of experimental kits based on EDIII-TBEV makes it possible to effectively detect IgG antibodies to tick-borne encephalitis virus and, in contrast to commercial tests, to differentiate them from antibodies to the pathogens of dengue, yellow and Zika tropical fevers. A recombinant analogue of domain III of the surface protein E in the tick-borne encephalitis virus can be a useful capture reagent when creating diagnostic test systems in the format of enzyme-linked immunosorbent assay and dot-immunoassay for the differentiated detection of IgG antibodies to the tick-borne encephalitis virus.